Socio-economic status of goat farmers in Gorakhpur district of Uttar Pradesh - SINGH, VIVEK PRATAP; SINGH, R P; SINGH, AVANISH K; SINGH, R K; UPADHYAY, S P; SRIVASTAVA, A K (The Indian Journal of Animal Sciences, 2021)
Goat rearing is an important source of livelihood particularly for landless labourers and marginal farmers across the country. Evidence has shown that majority of goat farmers belonged to landless and marginal categories. Majority of goat farmers’ annual income was between ` 10,001 to 20,000 and only 5% of farmers had an annual income of more than ` 50,000. Study also reveals that about 68% goats kept by farmers were from non-descript breed followed by Black Bengal (27%). Beside this nearly 14% of goat farmers were getting veterinary aid from government veterinary hospital while 86% of goat farmers were dependent on either private veterinarian or home remedies. Moreover, about 42% farmers were having hut type of houses for goat rearing. In the light of the results obtained it can be concluded that the production potential of goats could be enhanced with the introduction of superior technologies as well as improved practices which would help the farmers to contribute meaningfully to meet the needs of the family members and also improve the socioeconomic status of goat farmers.